2004
DOI: 10.1063/1.1704854
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a carrier supply layer on carrier density and drift mobility of AlGaN/GaN/SiC high-electron-mobility transistors

Abstract: Sheet carrier concentration and low-field drift mobility of intentionally undoped and modulation-doped AlGaN/GaN heterostructures on SiC substrate were evaluated by capacitance-voltage and channel conductivity measurements. Sheet carrier concentration and average mobility at 0 V gate bias correspond to standard Hall results. Sheet carrier density increases from 6.8×1012 cm−2 for the undoped sample up to 1×1013 cm−2 for the device with the highest doping concentration, while the mobility decreases from 1800 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 11 publications
3
14
0
Order By: Relevance
“…The low current level in I DS is mostly due to smaller contact area and ohmic contact formation. Utilizing a negative gate bias ( V GS ), the piezoresistive effect is translated into a piezotransistive effect where the 2DEG carrier concentration ( n s ) 27 is reduced, thus primarily increasing the Δ n s / n s ratio (Δ n s is the change in 2DEG concentration due to strain caused by deflection of the cantilever). Figure 2b shows the gate bias dependence of the 2DEG density, which was obtained for a particular gate bias by integrating the C – V characteristic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low current level in I DS is mostly due to smaller contact area and ohmic contact formation. Utilizing a negative gate bias ( V GS ), the piezoresistive effect is translated into a piezotransistive effect where the 2DEG carrier concentration ( n s ) 27 is reduced, thus primarily increasing the Δ n s / n s ratio (Δ n s is the change in 2DEG concentration due to strain caused by deflection of the cantilever). Figure 2b shows the gate bias dependence of the 2DEG density, which was obtained for a particular gate bias by integrating the C – V characteristic.…”
Section: Resultsmentioning
confidence: 99%
“… 24 ), the ratio Δ n s / n s will increase as the gate voltage becomes more negative and vice versa . Since μ int also decreases with reduced n int (due to increased scattering) 27 , the ratio Δ μ int / μ int will also increase with more negative gate voltage, causing Δ ρ int / ρ int to increase strongly as V GS becomes more negative. Clearly, to maximize Δ ρ int / ρ int , which ultimately controls the sensitivity, appropriate choice of V GS is very important.…”
Section: Resultsmentioning
confidence: 99%
“…3 Measurement results and discussion Hall measurements show an increase of the sheet carrier density n SHEET with increasing doping level from 7x10 12 to 9.7x10 12 cm -2 , while the Hall mobility µ HALL is reduced from 1930 down to 1670 cm 2 /Vs, as shown in Table 1. In a former work we have evaluated the mobility of the 2DEG by channel conductivity measurements on FATFET structures [4]. We observed that the mobility only depends on the actual sheet carrier concentration and is not influenced by the existence of a carrier supply layer.…”
Section: Introductionmentioning
confidence: 96%
“…The local mobility in Fig. 1 is defined as the mobility of the carriers that are added into the channel with gate voltage increase [4]. Obviously all three samples show the same dependence of the mobility on the 2DEG sheet concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Schottky barrier height 1.3 + 0.84 eV can be as high as 5 V. When the applied gate voltage is high, the conduction band near the AlGaN barrier layer will drop below the Fermi level which will significantly increase the carrier concentration of the AlGaN barrier layer. This phenomenon is also known as carrier spill-over and is reported in experimental work on the measurement of drift mobility and gate charge on AlGaN/GaN devices[83],[84].In order to model the carrier concentration of the AlGaN barrier layer, nb, the effective electric field in the AlGaN layer is used in a simplified Fermi-Dirac statistic by considering EF > ΔEC[85].The effective 2DEG carrier concentration at any point can be then modified from (4.1) as,…”
mentioning
confidence: 70%